Iterleukin-4 and interferon-in allergic contact dermatitis with atopic background in leather tannery factory worker - S Widhiati AS Siswati H Kariosentono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Immune response in allergic contact dermatitis (ACD) patient is dominated by T helper-1 (Th-1) response characterizedwith increase in interferon gamma (IFN-). However, in atopic individual, the immune response is dominated by Thelper-2 (Th-2) response which characterized with the presence of interleukin-4 (IL-4). Based on that condition, it ishypothesized that atopic individual was hardly to develope ACD. In leather factory, many workers are prone todevelope ACD. The aim of this study is to differentiate the cytokine profiles of IL-4 and IFN-of ACD patients withor without atopic background. Using a cross-sectional design, this study involved 30 subject assigned into twogroups, one group consisted of 15 subjects with ACD who had atopic background (ACD atopic), the other groupconsisted of 15 subjectswith ACD who had no atopic background (ACD non atopic). Both groups were examined bypatch test and confirmed to have ACD when the result was minimally+1 in 48 and/or 96 hours examination. Atopicskin diathesis score 8 was used to determine the possibility of having atopic background. Serum IL-4 and IFN-concentrationwere determined using ELISA. Data were analyzed using SPSS with Mann-Whitney non- parametrictest. The results showed that the mean value of IL-4 in both groups were 0.18±0.14 pg/mL and 0.25±0.29 pg/mL (p=0.917) whereas the mean value of IFN- in both groups were 13.03 ±23.90 pg/mL and 2.76±5.67 pg/mL, (p=0.096). In conclusion, the cytokine profiles of IL-4 and IFN-were not significantly different between ACDatopic and ACD non atopic individuals. This finding suggested that atopic and non-atopic individuals had a similarimmunologic response during development of ACD.Key words: immunologic response-cytokine-occupational contact dematitis-T helper-patch testing